Diseño 3D “environment isometric” representando las iglesias de Latacunga para difundir sus historias - Cruz Martínez, Omar Antony (2025)
This project has uncovered a significant issue within the city of Latacunga: its urban tourist attractions are vastly underutilized. Among these are colonial-era buildings, each holding historical archives that narrate the origins of an entire civilization. However, due to a lack of awareness about the true value of this heritage, much of it has been gradually lost over time. This project specifically focuses on those often overlooked yet historically rich sites, particularly the churches, some of which have borne witness to pivotal events in the city’s history. To highlight their significance, these structures were represented in 3D to inform the community in an engaging manner through infographics, social media posts, and brochures. The aim is to deepen understanding of the region’s history while fostering awareness about the value of its heritage to encourage its preservation. The history of each church included in this project was explored through bibliographic research. A qualitative methodology was employed, involving interviews with professionals in the field to identify effective approaches. Additionally, a quantitative method was applied through surveys to determine public preferences, which also helped to further reveal the core issue this project seeks to address.